Reelin promotes cerebral angiogenesis via mTOR/HIF-1α-mediated transcriptional upregulation of Netrin-4 - Zhaowei Feng; Meihua Pan; Hui Liu; Meiting Liu; Jiahui Yang; Chun-yu Wang; Ruiqin Yao; Haiyan Liu; Yanyan Fu (Tissue and Cell, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Particle-associated distribution, sedimentary accumulation, and SSD-based ecological risk assessment of organochlorine pesticides in the East China Sea - Jie Fu; Longkun Sun; Yan Zhang; Wenqing Wang; Zhongyu Cui; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Marine Environmental Research, 2026)

Building-scale seismic performance and resonance mitigation of variable-curvature sliding isolators under pulse-type ground motions - Lyan-Ywan Lu; Natalia Lioe; Pao-Chun Lin; Fu-Pei Hsiao (Soil Dynamics and Earthquake Engineering, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Iron-doped porous carbon derived from Fe-MOFs for activation of peroxymonosulfate to degrade organic pollutions - Wen Huang; Xin Chen; Yuhang Fu; Lei Chen; Ruizhen Li; Qijun Cao; Hongchen Ma; Jiangqiang Zhang; Chun wang (Journal of Environmental Chemical Engineering, 2026)

An eco-friendly and cost-effective method for leaching lithium from spent LiFePO4 batteries involves using wood vinegar as a leaching agent - Huynh Tri; Chia-Hung Su; Balaji Panchal; Chun-Chong Fu; Shao-Jung Wu; Horng-Yi Juan (Hydrometallurgy, 2026)

Role of pectin degree of esterification in the structural assembly and oxidative stability of WPI–citrus Pectin–EGCG conjugates stabilized emulsion - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Food Hydrocolloids, 2026)

Legacy-to-Alternative Shift of Brominated Flame Retardants in the East China Sea Revealed by Multimedia Observations and Coupled Modeling - Jie Fu; Xing Liu; Gu Tao; Haibo Zhang; Ye Kong; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Water Research, 2026)

An analytical model for liquefaction-induced underground buried structure uplift with experimental validation - Fu-Hsuan Yeh; Chun-Yu Hsu; Louis Ge; Siau Chen Chian (Tunnelling and Underground Space Technology, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Abietane diterpenoids and taraxerane-type triterpenes from Teucrium viscidum - Tong Xue; Chun Gao; Hao Chen; Muhi Eldeen Hussien Ibrahim; Hongzheng Fu; Jianbin Wang (Natural Product Research, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Machine-learning-assisted process interpretation of composting time across composting systems involving multiple organic wastes: Key explanatory contributions of temperature evolution during the cooling–maturation phase - Xia Yao; Weilin Fu; Chun Song; Xueyan Zhang; Shiyu Lv; Yongzhen Ding; Feng Wang (Journal of Environmental Management, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Self-crosslinking emulsion gels stabilized by thiolated pectin for high-efficiency curcumin encapsulation: A crosslinker-free strategy - Lv Ya-Nan; Wang Ping-Ping; Fu Xiong; Chen Chun (Food Chemistry, 2026)

The Role of Upper Body Motions in Stationary Ball-Kicking Motion: A Systematic Review - Junze Chen; Kerry Peek; Ross Howard Sanders; Jack Lee; Johnson Chun Yiu Pang; Kanchana Ekanayake; Allan Chak Lun Fu (Journal of Science in Sport and Exercise, 2026)
A ball-kicking motion requires a coordinated sequencing of all body segments for maximum ball release speed. Evidence of the role of upper body rotations and motor coordination during a ball-kicking motion is inconsistent among existing evidence. This study aimed to systematically review the role of upper body rotations on all modes of ball kicking and performance metrics. A comprehensive search of seven electronic databases from the inception was conducted. Studies reporting on the relationships between upper body rotation, and ball-kicking performance were included. From 1486 potentially relevant studies, we analysed 27 studies involving 457 participants. These studies encompassed instep soccer kicks ( n = 21), inside-of-the-foot soccer kicks ( n = 1), rugby place kicks ( n = 4) with a stationary ball, and a volley kick ( n = 1). Methodological quality assessment was performed using Standard Quality Assessment Criteria. Our results provide moderate evidence that increasing thoracolumbar rotations along the longitudinal axis and the transverse plane can enhance ball-releasing velocity through a "whip-like effect" based on the kinetic link principle. However, to gain a comprehensive understanding, further research is needed to explore the effects of timing and the ranges of motion of all relevant upper and lower body segments on ball release velocity and its potential influence on ball release accuracy. The current coaching manuals do not emphasise the significance of upper body rotation, indicating a pressing requirement for revisions in training guidelines to enhance ball-kicking performance.

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Dual-mode colorimetric and fluorescent pH sensor based on carbon dots for real-time monitoring of shrimp freshness - Ke Zhang; Pingping Wang; Haiming Chen; Chun Chen; Xiong Fu (Food Packaging and Shelf Life, 2026)

Heavy rainfall shifts microbial control from nutrient–temperature to precipitation dependence in subtropical coastal waters - Chien-Fu Chao; Madeline Olivia; Clara Natalie Annabel; Patrichka Wei-Yi Chen; Chih-hao Hsieh; Tzong-Yueh Chen; Feng-Hsun Chang; Pei-Chi Ho; Yi-Chun Yeh; Chia-Te Chien; Fuh-Kwo Shiah; Vladimir Mukhanov; et al. (Estuarine, Coastal and Shelf Science, 2026)

Electrocatalytic Hydrogen production from sulfide containing wastewater: Integration of resource recovery and renewable energy utilization - Chun Tang; Jie Fu; Chao Duan; Zhengyue Huang; Zhicheng Pan; Ying Zhou (Chemical Engineering Journal, 2026)

Functional Characterization of CLE Peptides in Cotton Root Development Reveals GhCLE47 as a Key Regulator of Auxin-Mediated Root Architecture - Gai-Yuan Hu; Peng Liao; Xin-Yao Jiang; Ying-Chao Tang; Ting-Wan Li; Yang Li; Fu-Chun Xu; Zhen-Nan Zhang (Journal of Plant Growth Regulation, 2026)

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Novel microfluidic gelatin-paper-based chip for sensitive colorimetric detection of urine albumin - Chien-Hsuan Ko; Chin-Chung Tseng; Hsing-Meng Wang; Chia-Chun Lee; Cheng-Xue Yu; Lung-Ming Fu (Analytica Chimica Acta, 2026)

Ultrasonic degradation of Dendrobium officinale polysaccharide: Kinetics, structural modification, and its impact on wheat starch digestibility - Jinfeng Fu; Xiong Fu; Pingping Wang; Yuxuan Fu; Chun Chen (Food Research International, 2026)

Comprehensive Comparison on Potentially Toxic Elements Between Sandstorm PM2.5 and Haze PM2.5 - Jiaojiao Xie; Yixian Long; Songyao Liu; Yiran Fu; Chun-Gang Yuan; Mingyu Li; Shuang Deng (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Three-dimensional cell culture in vitro could better recapitulate the biological behavior of cells in vivo - Zhihao Qi; Shuhua Yang; Chun Fu; Junjie Xu; Quan Li; Junfang Yan; Aihua Shen; Burong Hu (Tissue and Cell, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Multi-stage pretreatment coupled with microwave-assisted formic acid hydrolysis for green preparation of xylose residue-based cellulose nanofibers - Haolong Zhang; Wenjing Bu; Ruimin Guo; Sai Zhang; Kai Fu; Zhining Li; Guizhuan Xu; Xiaoyang Zheng; Wei Chen; Chun Chang (Sustainable Chemistry and Pharmacy, 2026)

Corrigendum to “Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China” [Sci. Total. Environ., Volume 874 (2023), 162397] - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Ruichang Shen (Science of The Total Environment, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

A structural-preserving and scalable EBI strategy for functional cellulose copolymer films - Zhining Li; Liqin Yu; Shiqiang Zhao; Zhen Ma; Kai Fu; Haoyu Li; Haolong Zhang; Xiao Li; Yi Fan; Chun Chang (Chemical Engineering Journal, 2026)

Unveiling the mechanisms of mechanical stirring for enhanced performance and stability of algal-bacterial flocs treating low C/N synthetic wastewater - Jun-Jie Gu; Bin-Di Mao; Xiao-Xiao Dou; Bin-Xin Zhang; Jia-Wei Xu; Chun-Wan Fu; Bang-Jie Lan; Xin-Jie Zhang; Zhe Xu; Feng Gao (Bioresource Technology, 2026)

Synergistic binary acidity in metal sulfates drives efficient alcoholysis of high-solid xylose residues: An experimental and DFT investigation - Chun Chang; Xin Liu; Shuo Zang; Kai Fu; Zhen Ma; Xiaoyang Zheng; Huijuan Tian; Zhining Li (Biomass and Bioenergy, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Correction: Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Fracture identification in hot dry rock using TSD-Unet: From feature extraction to quantitative analysis of geometric parameters - Mangu Hu; Tianyu Fu; Xiaobin Yang; Lei Peng; Chun Wang; Xiangfeng Lv (Geothermics, 2026)

Nitrogen-phosphorus co-doped carbon layer-confined ultra-thin self-grown polyphase molybdates heterojunction nanosheet arrays for efficient water splitting - Lan Zhang; Rao Fu; Ke Chen; Xi Peng; Li Zhang; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; et al. (Fuel, 2026)

Key structural characteristics enhancing digestion resistance in rice starch-sugarcane polyphenols complexes - Zhang Tong; Li Jia-Jiong; Fu Xiong; Wang Ping-Ping; Chen Hai-Ming; Chen Chun (Food Chemistry, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Antifouling compounds from marine fungus Aspergillus iizukae GXIMD 00548 - Chun-Qing Fu; Meng-Fan Qi; Chun-Xiao Chen; Hua-Qing Huang; Xiao-Wei Luo; Cheng-Hai Gao; Yong-Hong Liu; Xin-Ya Xu (Biofouling, 2026)

Optimizing environmental surveillance for early detection of zoonotic pathogens via fecal shedding modeling - Xin Du; Zhiqiang Deng; Yuqing Long; Fenglan He; Chunlong Zhu; Chun Han; Hui Li; Songzhe Fu (Water Research, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Silica reversal reveals the lithium super-enrichment during the extreme differentiation of granitic magmas - Chun-Li Guo; Roberto F. Weinberg; Fu-Yuan Wu; Jun-Xing Zhao; Xiao-Chi Liu; Bin-Wu Zhang (Lithos, 2026)

Vegetation greenness and productivity recovery following the 2022 record-breaking compound soil moisture and atmospheric drought in Yangtze River Basin - Huiming Han; Chun Fu (Journal of Hydrology, 2026)

Characterization and influencing factors of hydroxymethanesulfonate (HMS) in the North China plain: integration of field measurements and theoretical calculations - Chun Chen; Haijie Zhang; Yele Sun; Junling Li; Zhiqiang Zhang; Jian Gao; Rui Gao; Lianfang Wei; Nan Ma; Wanyun Xu; Pingqing Fu (Atmospheric Environment, 2026)

Spatiotemporal changes in dissolved organic matter chemodiversity and its interaction with microbial composition in heavy-metal polluted river - Chun Liu; Rujie Li; Yuheng Zhang; Lijie Zhang; Zhaoling Liu; Ping Li; Guanghui Fan; Yingjie Zhu; Yue Zuo; Xule Liu; Zhiyong Fu; Xiufeng Zhang (Water Research, 2026)

Rational design of Whey protein–polysaccharide delivery systems: Synergistic mechanisms and advanced applications - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Trends in Food Science & Technology, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Degradation of organic refractory contaminants by phosphate buffer activated peroxymonosulfate: The overlooked roles of oxygen reactive species - Qing Liu; Siying Long; Xiaodi Duan; Qiqi Zhu; Qing Fu; Wei Wang; Jiarui Shi; Yaqi Wang; Chun Cai (Journal of Cleaner Production, 2026)

Influence of pyrolysis on biomass structure: microscopic deformation patterns and chemical composition variations - Shao-Hua Sun; Jiang Wan; Hui-Chun Fu; Yong-Huan Sun; Feng Shao; De-Sen Ni; Jian-Jiang Lu (Fuel, 2026)

Sugarcane extract enhances stress resilience and longevity in Caenorhabditis elegans: NMR structural elucidation and transcriptomic mechanisms - Dong Yu-Hao; Chen Chun; Wang Ping-Ping; Wang Chun; Fu Xiong (Food Research International, 2026)

Self-assembled nanoparticles from sugarcane polyphenol compounds for enhanced antioxidant activity and in vivo absorption - Zhang Tong; Fang Jia-Qin; Fu Xiong; Wang Ping-Ping; Wang Chun; Fu Yu-Xuan; Chen Chun (Food Research International, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Baicalin-aluminum complexes inhibit growth and suppress virulence of enterotoxigenic Escherichia coli in vitro - Chun Ye; Xingyue Li; Yunqi Liu; Yuqian Chen; Ming Zhao; Ronghua Yin; Qirong Lu; Jin Liu; Yu Liu; Shulin Fu; Yinsheng Qiu (Toxicon, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Cross-domain disaggregation of electricity for heating in all-electric school buildings – learning from school buildings with district heating - Synne Krekling Lien; Ada Canaydin; Clayton Miller; Chun Fu; Hussain Kazmi; Jayaprakash Rajasekharan (Energy and Buildings, 2025)

Ohmic contact interface engineering of fullerene-derived long-range ordered porous carbon-based anodes for durable sodium-ion capacitors - Jundong Shao; Mingming Gao; Ying Huang; Songlin Liu; Junke Li; Xiaosong Xiong; Antonio Gaetano Ricciardulli; Sheng Yang; Yubin Fu; Faxing Wang; Chun Fang; Panpan Zhang; et al. (Chemical Engineering Journal, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2025)
Methylmercury (MeHg) is a potent neurotoxin and bioaccumulates in food webs. Microbial transformation of inorganic mercury (Hg) produces most of the MeHg in the marine environment. The gene pair hgcAB encodes for Hg methylation, a process predominantly attributed to anaerobic bacteria. However, recent studies indicate the formation of methylmercury in low-oxygen zones within marine water columns, although the mechanisms remain poorly understood. “Blue holes” are marine sinkholes containing redox gradients stratified with depth and high microbial diversity across a range of biogeochemical cycles. Here, we present the first metagenomic analysis focused on the potential for Hg methylation in a blue hole ecosystem. Yongle Blue Hole (YBH), currently the world’s deepest known blue hole, was selected as a representative site to investigate the genetic potential for Hg methylation and to explore the functional capabilities of putative Hg-methylators within this unique environment. Metagenomic analysis showed that the anoxic sulfidic deep water was likely to be a hotspot for Hg methylation, driven by abundant and diverse Deltaproteobacteria. In the suboxic intermediate layer, Nitrospina and Myxococcota dominated the Hg-methylating community. Furthermore, Hg methylators were found to have different lifestyles (free-living or particle-associated) and to occupy distinct ecological niches within the YBH. In addition, the contribution of sinking particles to Hg methylation, especially in the deep anoxic water column, was highlighted. Our study unveils the biodiversity and survival strategies of Hg methylators across distinct environments. The findings suggest that blue holes could serve as model stratified ecosystems for studying Hg methylation processes across different habitats.

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Deproteinization and controlled starch prehydrolysis in intact pulse cotyledon cells regulates starch retrogradation and digestion - Minghao Mao; Mario M. Martinez; Yunus Emre Tunçil; Li Ding; Chun Chen; Xiong Fu; Qiang Huang; Bin Zhang (Carbohydrate Polymers, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Identification and characterization of miRNAs and targets in two poplar varieties with different resistance in responses to Anoplophora glabripennis (Coleoptera) infestation - Zeqi Wang; Tiantian Fu; Chun Wang; Yuzhang Yang; Xiaoqian Yang; Jiahao Liu; Ruen Yu; Hongkun Ji; Yuanlong Wang; Tianliang Wang; Jieru Li; Yanwei Wang (Plant Science, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

The impact of the interaction between trace chloramphenicol, biofilm, and corrosion products on disinfection by-products and microbial risks in chlorinated drinking water distribution systems - Xinkai Liu; Yanliang Lin; Kaifeng Shen; Youyi Chen; Pojun Zhang; Zihui Chen; Yaning Zhang; Jing Huang; Leixuan Fu; Sibo Liu; Chun Hu; Xueci Xing; et al. (Journal of Water Process Engineering, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Efficient activation of peracetic acid by Fe-doped g-C3N4 for selective degradation of emerging contaminants: Unraveling the role of reactive complex - Chun Cai; Jiarui Shi; Qing Liu; Qiqi Zhu; Qing Fu; Wei Wang; Xiaodi Duan (Journal of Hazardous Materials, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

A review of municipal sewage sludge biological material applications in biofuel and environmental pollution control and future opportunities - Balaji Panchal; Chia-Hung Su; Chun-Chong Fu; Shao-Jung Wu; Horng-Yi Juan (Journal of Environmental Chemical Engineering, 2025)

Emission prediction of diesel /n-hexanol blended fuels with graphene oxide addition based on ITCN-TSO model - Yuede Pan; Changcheng Fu; Jinkai Gu; Kaifeng Zhong; Hao Chen; Zhenhua Ji; Li Li; Mingzhang Pan; Chun Ma; Wei Guan (Journal of Environmental Chemical Engineering, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Functional characterization of RNAi candidate target genes in Monolepta hieroglyphica (Motschulsky) for potential pest control applications - Xu Chen; Ning Fu; Qingxuan Xu; Chun Zhang; Su Wang; Da Xiao (Journal of Asia-Pacific Entomology, 2025)

Design of protein-based carriers for curcumin with tailored particle properties: Stability and mechanistic insights - Wenting Huang; Zhiping Hong; Zhijie Fu; Chun Meng; Yuhong Mao (Food Chemistry, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Delivery of penetration-enhancing antioxidant polyphenol nanoparticles with Codonopsis pilosula polysaccharide microneedles for synergistic treatment of psoriasis - Siqi Liu; Silu Song; Yu Zhang; Liming Yan; Yuhui Chen; Wanrong Li; Banaz Jalil; Chun Wu; Yuping Fu; Xingfu Chen; Jingyi Gu; Lixia Li; et al. (Carbohydrate Polymers, 2025)

Carnosic Acid Attenuated the Motor Impairment by Bisphenol A is Related to the Regulation of Autophagy Through Parkin in In Vitro and In Vivo - Chun-Huei Liao; Ya-Chen Shih; Hsi-Yun Huang; Jing-Wei Chen; Shao-I Hsu; Chiao-Ni Lai; Ru-Huei Fu; Chia-Wen Tsai (Molecular Neurobiology, 2025)

Selection of microRNA expression reference genes for RT-qPCR in poplar root under low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Jiahao Liu; Siyu Hou; Yiyi Yin; Xiaoqian Yang; Dandan Xiao; Yanwei Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Integrated LC-MS/MS, Network Pharmacology, and Experimental Validation Reveal the Mechanism of Eucommia Ulmoides against Osteoarthritis - Danqing Fu; Chun Gan; Shiyu Gao; Jialu Shu; Shenman Zhou; Ke Zhou; Zhenyan Peng; Haoqiang Dai; Chenjie Xia (Cell Biochemistry and Biophysics, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Analysis of the response mechanism in lipid degradation of key gene LDH1 knockout strains of Saccharomyces cerevisiae under levulinic acid stress - Yulei Chen; Jiaye Tang; Qian Li; Wenli Xin; Ximeng Xiao; Borui Mou; Jialian Li; Fujia Lu; Chun Fu; Wencong Long; Hong Liao; Xuebing Han; et al. (Archives of Microbiology, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

An empirical exploration of the capacity of choline chloride/lactic acid eutectics to extract and stabilize natural polyhydroxy compounds - Yanhong Bi; Ruiping Fu; Weiliang Hua; Xinyu Xiong; Chun Zhu; Xiaobao Nie; Zhaoyu Wang (Food Chemistry, 2025)

Olfactory receptors and human diseases - Zhong-Qi Yuan; Xiao-Chun Peng; Lian Liu; Fu-Yuan Yang; Feng Qian (Cell and Tissue Research, 2025)

Vegetation change mechanism and key driving factors in complex terrains, China - Kewen Wang; Chun Fu; Changsen Zhao; Tianming Zhou; Yanqing Lian; Guoqing Wang (Science of The Total Environment, 2025)

New thiohydantoin derivatives from the roots of Lepidium meyenii - Wen-Xin Liu; Jun Li; Cheng-Juan Liao; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Chemical composition, antioxidant activity, α-glucosidase inhibitory activity, and metabolomic profiling of Dendrobium officinale across diverse growing regions and cultivation modes - Shu He; Zhengli Lu; Rurui Li; Chun Chen; Xiong Fu; Kin Weng Kong; Amin Ismail; Xuechun Zhang; Zhenxing Wang (Food Bioscience, 2025)

Bytes drive green: decoding the global digital economy’s environmental impact - Gen-Fu Feng; Ping-Chuan Jiang; Zhu-jia Yin; Chun-Ping Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Degradation of N-methylbenzylamine and N,N-dimethylbenzylamine in anaerobic biological reactors and formation of N-nitrosomethylbenzylamine and N-nitrosodimethylamine during subsequent chloramination - Iresha Premarathne; Shih-Wen Peng; Yu-Chun Tseng; Guan-Fu Chen; Yu-Jih Su; Wei-Hsiang Chen (Journal of Hazardous Materials, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Virtual screening and characterization an umami/umami-enhancing peptide from chickpea - Yakun Song; Qingjing Liu; Weiling Mo; Jianan Zhang; Xiangjin Fu; Chun Liu (Food and Humanity, 2025)

3D printing of synthetic microbial consortium for boosting bioelectricity generation from starch - Xiao-Jing Wang; Jie Wang; Zhizhi Yang; Ye Zhang; Kai Cheng; Jun-Ying Han; Fu-Xiang Chang; Yang-Chun Yong (Chemical Engineering Journal, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Five-year-old children with autism spectrum disorders struggle with disengaging attention - Wei Wang; Chun Cheng; Zhiyu Xu; Licheng Xue; Wanlu Fu; Jing Zhao (Cognitive Processing, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

miRNA-seq analysis revealed a potential strategy underlying poplar root responses to low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Siyu Hou; Kaijing Rong; Jing Wang; Yiyi Yin; Xiaoqian Yang; Ruen Yu; Dandan Xiao; Yanwei Wang (Planta, 2025)

Re-exploration of phenolic compounds from natural waste rice husks: Combined synthesis of novel herbicide and evaluation of herbicidal activity - Li-xia Zhao; Ruo-nan Song; Jing-yi Li; Yue-chun Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2025)

Interactions between riverine sediment organic matter molecular structure and microbial community as regulated by heavy metals - Ping Li; Chun Liu; Lijie Zhang; Zhaoling Liu; Zhiyong Fu; Guanghui Fan; Yingjie Zhu; Yue Zuo; Liqiong Li; Lisha Zhang (Journal of Hazardous Materials, 2025)

Glycolysis of waste polyurethane foam for preparing recycled polymer materials: Optimization and techno-economic evaluation - Chun Chang; Youfeng Jiang; Yucheng Lin; Kai Fu; Chunbao Xu; Shiqiang Zhao (Chemical Engineering Journal, 2025)

Atomically dispersed bimetallic single-atom Cu, Fe/NC as pH-universal ORR electrocatalyst - Weiming Gong; Peng Guo; Lan Zhang; Rao Fu; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; Zhiwei Lu (Chemical Engineering Journal, 2025)

Acute caffeine supplementation offsets the impairment in 10-km running performance following one night of partial sleep deprivation: a randomized controlled crossover trial - Yi-Shan Tsai; Ting-Tzu Chen; Yau-Ching Chan; Chun-Chin Huang; Ting-Fu Lai; Yung Liao; Richard S. Metcalfe; Yung-Chih Chen; Ho-Seng Wang (European Journal of Applied Physiology, 2025)

Morphology and molecular analysis of Heterodera camelliae n. sp. (Nematoda: Heteroderinae), a new species of cyst‑forming nematode parasitizing tea plants in China - Chun-Hui Ni; Qian-Ying Li; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

Role of the clock gene period in regulating circadian rhythm of courtship vibrations in Nilaparvata lugens - Qi Wei; Jia-Chun He; Wei-Xia Wang; Feng-Xiang Lai; Pin-Jun Wan; Qiang Fu (Insect Biochemistry and Molecular Biology, 2025)

Effect of ambient ozone and its interactions with ambient PM2.5 and temperature on peak expiratory flow in adults with asthma - Dongxia Jiang; Ying Shang; Zhengxiong Li; Xianlin Mu; Xuehu Han; Xinzhuo Xie; Guanglong Fu; Yunshu Zhang; Shaodan Huang; Chun Chang (Atmospheric Environment, 2025)

Transcriptome-wide identification of MYB gene family and functional analysis of LcsMYB123 in Litsea coreana var. sinensis - Na Xie; Qiqiang Guo; Mengyun Liao; Yang Xiao; Chun Fu; Yunxin An (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

QTL mapping and candidate gene identification for lower temperature tolerance and growth traits using whole genome re-sequencing in Argopecten scallops - Fu-Kai Wang; Pei-Can Zhu; Xiao-Tong Zhang; Kai Yu; Chun-De Wang; Bo Liu (Aquaculture, 2025)

Laser flash pyrolysis of face mask waste to vinylidene-terminated PP wax and further functionalized as compatibilizer - Hao-Qin Zhang; Lun Chen; Chang-Qian Chen; Fu-Lu Chang; Yi-Xun Tian; Xia Jiang; Wei-Tao Huang; Bin Hu; Xian-Wu Cao; Xiao-Chun Yin; Guang-Jian He (Waste Management, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Dust resuspension from contaminated fabrics subjected to force-induced vibrations - Jie Feng; Ka Chung Chan; Chun-Ho Liu; Christopher Y.H. Chao; Sau Chung Fu (Journal of Aerosol Science, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Intrathecal Fumagillin Alleviates Chronic Neuropathy-Induced Nociceptive Sensitization and Modulates Spinal Astrocyte-Neuronal Glycolytic and Angiogenic Proteins - Zhi-Hong Wen; Zong-Sheng Wu; Hao-Jung Cheng; Shi-Ying Huang; Shih-Hsuan Tang; Wei-Nung Teng; Fu-Wei Su; Nan-Fu Chen; Chun-Sung Sung (Molecular Neurobiology, 2025)

Modelling of mass transport in fractured crystalline rock using velocity interpolation and cell-jump particle tracking methods - Chieh-Chun Chang; Yi-Fu Chiou; Yu-Hsiang Shen; Yun-Chen Yu (Geomechanics for Energy and the Environment, 2024)

Advances in structure-hypoglycemic activity relationship and mechanisms of berry polysaccharides - Su Jiang-Peng; Fang Jia-Qin; Liu Chuang; Liu Shou-Ping; Chen Chun; Tan Chin-Ping; Wang Ping-Ping; Peng Yun-Ping; Fu Xiong (Food Bioscience, 2024)

Characterization of core microbiota of barley seeds from different continents for origin tracing and quarantine pathogen assessment - Xin Zhou; Fang Liu; Chun-Chun Wang; Hui-Li Zhang; Peng Zhao; Fu-Hong Xie; Dian-Ming Hu; Wei-Jun Duan; Lei Cai (Food Microbiology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Konjac glucomannan exerts regulatory effects on macrophages and its applications in biomedical engineering - Xi Pan; Qida Zong; Chun Liu; Huiying Wu; Bo Fu; Ye Wang; Wei Sun; Yinglei Zhai (Carbohydrate Polymers, 2024)

Correction to: An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

A single‐nucleus transcriptomic atlas characterizes cell types and their molecular features in the ovary of adult Nile tilapia - Zhi Lei Yao; Xiao Wang; Chun Lei Hu; Fu Xiao Chen; Hong Ju Chen; Shi‐Jin Jiang; Yan Zhao; Xiang Shan Ji (Journal of Fish Biology, 2024)
In fish species, there is limited analysis of signature transcriptome profiles at the single‐cell level in gonadal cells. Here, the molecular signatures of distinct ovarian cell categories in adult Nile tilapia ( Oreochromis niloticus ) were analysed using single‐nucleus RNA sequencing (snRNA‐seq). We identified four cell types (oogonia, oocytes, granulosa cell, and thecal cell) based on their specifically expressed genes and biological functions. Similarly, we found some key pathways involved in ovarian development that may affect germline–somatic interactions. A cell‐to‐cell communication network between the distinct cell types was constructed. We found that the bidirectional communication is mandatory for the development of germ cells and somatic cells in fish ovaries, and the granulosa cells and thecal cells play a central regulating role in the cell network in fish ovary. Additionally, we identified some novel candidate marker genes for various types of ovarian cells and also validated them using in situ hybridization. Our work reveals an ovarian atlas at the cellular and molecular levels and contributes to providing insights into oogenesis and gonad development in fish.

Improvements in source apportionment of multiple time-resolved PM2.5 inorganic and organic speciation measurements using constrained Positive Matrix Factorization - Chun-Sheng Huang; Yi-Hsien Liu; Ho-Tang Liao; Chia-Yang Chen; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Tick saliva interference with LTβR signaling facilitates the transmission of Lyme disease spirochetes - Lin Jin; Bao-Gui Jiang; Yizhu Yin; Jingya Guo; Jia-Fu Jiang; Xiaopeng Qi; Gary Crispell; Shahid Karim; Wu-Chun Cao; Ren Lai (Toxicon, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Integrating spatially distributed data into Positive Matrix Factorization to identify the hotspots of local emission sources - Chun-Sheng Huang; Ho-Tang Liao; Chang-Fu Wu (Atmospheric Research, 2024)

Controls on the facies and architecture evolution of a fan delta in Qinghai Lake, China - Di Ma; Xinghe Yu; Shunli Li; Zhijie Zhang; Chao Fu; Hongwei Sun; Chun Liu (Frontiers of Earth Science, 2024)

Physiological and behavioral responses to social isolation and starvation in a social fish - Dan-Dan Xu; Chun-Hua Wang; Jin-Qiu Bi; Huan Luo; Shi-Jian Fu; Bin Li; Ling-Qing Zeng (Applied Animal Behaviour Science, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Applying the total carbon–black carbon approach method to investigate the characteristics of primary and secondary carbonaceous aerosols in ambient PM2.5 in northern Taiwan - Ankita Katoch; Muneer Abbass; Yi-Wen Chen; Thi Phuong Thao Ho; Chun-Fu Fan; Yu-Hsiang Cheng (Science of The Total Environment, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Solid-state fermentation of Limosilactobacillus fermentum and lysine addition to improve the cooking and eating quality of high-fiber rice noodles - Yakun Song; Jing Lin; Lijuan Luo; Zihan Chen; Weiling Mo; Xiangjin Fu; Chun Liu (Journal of Cereal Science, 2024)

A micromechanical analysis of marble pulverization under quasi-static progressive cyclic loading - Bin Fu; Yingchun Li; Chun'an Tang; Yinlin Ji; Arno Zang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

A structure-functionality insight into the bioactivity of microbial polysaccharides toward biomedical applications: A review - Hongxing Zhang; Yan Li; Yinyi Fu; Haixin Jiao; Xiangyu Wang; Qianqian Wang; Mengbo Zhou; Yang-chun Yong; Jun Liu (Carbohydrate Polymers, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Optical properties and molecular compositions of dissolved organic matter in multiple runoff components during rainfalls on the karst hillslope - Yuheng Zhang; Chun Liu; Zhiyong Fu; Hongsong Chen; Chunhuan He; Kelin Wang; Ping Li (Water Research, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Creating synthetic energy meter data using conditional diffusion and building metadata - Chun Fu; Hussain Kazmi; Matias Quintana; Clayton Miller (Energy and Buildings, 2024)

Robustness of design flood estimates under nonstationary conditions: parameter sensitivity perspective - Bin Xiong; Shuchen Zheng; Qiumei Ma; Chun Fu; Tianfu Wen; Zhongzheng He; Lingqi Li; Chong-Yu Xu (Stochastic Environmental Research and Risk Assessment, 2024)
The changing frequency of flooding in global watersheds, driven by various human and natural factors like land use/cover changes and global warming, necessitates innovative approaches in flood frequency analysis and risk assessment. Nonetheless, the reliability of nonstationary frequency analysis models remains a concern given challenges in accurately measuring the uncertainty introduced by these methods and the impact on design flood values. In this study, deviation-based differential sensitivity indices, including single-parameter (SDDSI) and entire-parameter (EDDSI) measures were developed to assess the influence of parameter uncertainty in nonstationary models using Bayesian statistics and "equivalent reliability" nonstationary design. The Weihe River, the largest tributary of the Yellow River which is experiencing both climate change and heavy impact of human activities, is chosen to be the study area to investigate the impact of precipitation change and land use change on nonstationary flood frequency. Results show that in the One-At-A-Time (OAT) sensitivity analysis under a small uncertainty scenario (SUS) for parameter inputs, the shape parameter stands out as the most influential factor (SDDSI_SUS = 0.347) affecting the 100-year design flood in the Stationary Generalized Extreme Value (SGEV) model. For the Non-Stationary GEV (NGEV) models, the influence of this parameter is less pronounced, with SDDSI_SUS values of 0.095 and 0.093 for the SSP126 and SSP585 scenarios, respectively. Instead, attention turns to the regression coefficient of the grassland area, associated with the GEV scale parameter. In global sensitivity analysis under the posterior uncertainty scenario (PUS) for parameter inputs, the EDDSI_PUS values for SGEV, NGEV_SSP126, and NGEV_SSP585 models were 0.52, 1.41, and 1.30, respectively, inferring heightened sensitivity of NGEV models to perturbations from entire parameters. It is anticipated that incorporating additional evidence, such as historical flood data, is essential for accurate nonstationary hydrological design to mitigating the influence of parameter uncertainty. The sensitivity indices in this study provide significant insights for assessing the robustness of nonstationary hydrological design in flood risk management and applications.

Were oxygen isotopes of hydrothermally altered minerals just elevated by the 18O-enriched water? Theoretical inversion with thermodynamics and kinetics - Chun-Sheng Wei; Zi-Fu Zhao (Mineralogy and Petrology, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

Using network pharmacology and molecular docking to uncover the mechanism by which quercetin alleviates deoxynivalenol-induced porcine intestinal injury - Pu Guo; Xuemin Li; Yunda Xue; Qirong Lu; Yu Liu; Jianglin Xiong; Zhongyuan Wu; Shulin Fu; Chun Ye; Xu Wang; Yinsheng Qiu (Toxicon, 2024)

Opening the Black Box: Towards inherently interpretable energy data imputation models using building physics insight - Antonio Liguori; Matias Quintana; Chun Fu; Clayton Miller; Jérôme Frisch; Christoph van Treeck (Energy and Buildings, 2024)

Cactodera guizhouensis n. sp. (Nematoda: Heteroderinae), a new species of cyst-forming nematode parasitizing potato in Guizhou, China - Chun-Hui Ni; Yu-Jia Xie; Si-Hua Yang; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2024)

Development and Application of an Industrial Wastewater Profile Database - Pei-Yuan Hsieh; Gen-Shuh Wang; Wen-Huey Mi; Chun-Sheng Huang; Chang-Fu Wu (Water, Air, & Soil Pollution, 2024)

Towards standardizing automated image analysis with artificial intelligence for biodiversity - Peng Zhou; Yu-Xin Bu; Ge-Yi Fu; Chun-Sheng Wang; Xue-Wei Xu; Xiaoyong Pan (Frontiers in Marine Science, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Light on multi-mode optical properties of carbon dots through rational surface engineering tuning strategies - Runfang Pei; Pinyi He; Fu Qin; Jianlong Ma; Cuixing Xu; Libo Qin; Wei Gao; Chun Han; Xinyu Wang; Xu Yu; Jianliang Bai; Zhijun Wang; et al. (Chemical Engineering Journal, 2024)

High-density bin-based genetic map reveals a 530-kb chromosome segment derived from wild peanut contributing to late leaf spot resistance - Jiaowen Pan; Xiaojie Li; Chun Fu; Jianxin Bian; Zhenyu Wang; Conghui Yu; Xiaoqin Liu; Guanghao Wang; Ruizheng Tian; Xiaofeng Song; Changsheng Li; Han Xia; et al. (Theoretical and Applied Genetics, 2024)

Navigating Safety and Compliance in High-Voltage Shore Connection Systems: A Comprehensive Exploration of IEC/IEEE 80005-1 Standards and the Guidelines of Ship Classification Societies - Shih-Hsien Hsu; Fu-Ming Tzu; Yi-Dong Chen; Chun-Wei Huang (Journal of Marine Science and Engineering, 2024)
This paper addresses the growing concern over air pollutant emissions (NOx, SOx, PM, CO2) from ocean-going vessels in harbor areas and the role of Onshore Power Supply (OPS) systems in mitigating these emissions during vessel berthing. However, the slow progress in global shore power facilities is attributed to safety- and specification-related concerns. Our study conducts a comprehensive analysis, comparing international shore power regulations, with a specific focus on the IEC/IEEE 80005-1 standard and guidelines from various ship classification societies. We introduce checklists, scoring tables, and spider diagrams to evaluate the regulatory content, highlighting the strengths and weaknesses of each approach. Furthermore, this paper emphasizes the significance of a well-defined operational process for high-voltage shore connection (HVSC) to ensure the safety of OPS operations. We present process diagrams for key operational stages, based on IEC/IEEE 80005-1 specifications and evaluation criteria. The ultimate goal of this research is to drive the global adoption of shore power and foster the establishment of shore power facilities worldwide. This aligns with the broader environmental protection objectives of achieving cleaner ports and reducing emissions for a sustainable future.

Baicalin attenuates lipopolysaccharide-induced intestinal inflammatory injury via suppressing PARP1-mediated NF-κB and NLRP3 signalling pathway - Qirong Lu; Nan Wang; Defeng Wen; Pu Guo; Yu Liu; Shulin Fu; Chun Ye; Zhongyuan Wu; Yinsheng Qiu (Toxicon, 2024)

Robust topological superconductivity in spin–orbit coupled systems at higher-order van Hove filling - Xinloong Han; Jun Zhan; Fu-Chun Zhang; Jiangping Hu; Xianxin Wu (Science Bulletin, 2024)

Nutrient recovery and pollutant removal using carboxymethyl cellulose/microfibrillated cellulose hydrogel: Templating effects of CaCO3 nanoparticles - Jialin Fu; Choe Peng Leo; Chun Kiat Chang (Journal of Water Process Engineering, 2024)

Dual strategy of ultrasound and doping enhance Mott Schottky heterojunction carrier exchange for efficient oxygen evolution - Yi-Wen Dong; Qian-Xi Lv; Bao-Hua Chen; Zheng-Yang Jin; Jing-Yi Xie; Fu-Li Wang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Synthesis and cytotoxic activity of ethyl ferulate derivatives as potent anti-inflammatory agents - Dan-ni Fu; Zi-yi Kong; Wen Sun; Chun-mei Bai; Yun Wu; Ming Bian; Qian-qian Ma (Natural Product Research, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Quaternary ammonium-functionalized rosin-derived resin for the high-performance capture of caramels: Experiments and quantum chemical theory simulations - Li Jiao; Wei Wei; Chun-Yu Liao; Yan-Hong Wei; Fu-Hou Lei; Wen Li (Journal of Hazardous Materials, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Origin and tectonic environment of the Longbohe Fe-Cu-(LREE) deposit in the Ailao Shan–Red River shear zone, Southwest China: a Neoproterozoic subduction-related IOCG deposit? - Lei Liu; Wei Terry Chen; Xiao-Chun Li; Xin-Fu Zhao (Mineralium Deposita, 2024)

Triplex visual detection of tobacco potyviruses using reverse transcription recombinase polymerase amplification assay combined with lateral flow dipstick - Tengzhi Xu; Xingwei Lin; Xiaolian Zhang; Yong Fu; Hao Luo; Chun Luo; Zhengduo Luo; Lei Lei; Meng-ao Jia (Crop Protection, 2023)

Metal-organic frameworks (MOFs)-derived Mn2SnO4@C anode based on dual lithium storage mechanism for high-performance lithium-ion capacitors - You-Kang Duan; Zhi-Wei Li; Shi-Chun Zhang; Tong Su; Yan-Fang Ma; Ai-Jun Jiao; Zhen-Hai Fu (Chemical Engineering Journal, 2023)

Effects of simulated warming on soil properties and bacterial community composition in the Bashania faberi ecosystem - Jianchao Fu; Jun Wu; Min Xu; Jing Ma; Lulu Long; Chao Chen; Gang Yang; Chun Song; Xiaohong Zhang; Hongbo Yang; Jindong Zhang (Applied Soil Ecology, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Drivers of low-carbon practices in green supply chain management in construction industry: An empirical study in China - Chun Fu; Ya-Qi Liu; Ming Shan (Journal of Cleaner Production, 2023)

Class 1 integron carrying qacEΔ1 gene confers resistance to disinfectant and antibiotics in Salmonella - Shujuan Chen; Jingxia Fu; Ke Zhao; Shengzhi Yang; Chun Li; Petri Penttinen; Xiaolin Ao; Aiping Liu; Kaidi Hu; Jianlong Li; Yong Yang; Shuliang Liu; et al. (International Journal of Food Microbiology, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Aristolochic alkaloids from Piper macropodum and their anti-inflammatory activities - Chun-Yue Liu; Yong-Fu Lu; Si-Xuan Liu; Yong-Fu Li; Yan Dong; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Kinetin inhibits hepatic stellate cell activation and induces apoptosis via interactions with the TGF-β1/Smad signaling pathway - Fu-chang Jin; Jing-jing Chen; Qiu-xian Xu; Ming-Hui Zhou; Yi Lin; Qi-wei Zhang; Chang-chun Zhang; Zhen-gang Zhang (Toxicology and Applied Pharmacology, 2023)

Comparative transcriptome analysis of grafting to improve chilling tolerance of cucumber - Xin Fu; Chun-Yu Lv; Yan-Yan Zhang; Xi-Zhen Ai; Huan-Gai Bi (Protoplasma, 2023)

Driving forces and their interactions of soil erosion in soil and water conservation regionalization at the county scale with a high cultivation rate - Bang-lin Luo; Jiang-wen Li; Chun-ming Gong; Shou-qin Zhong; Chao-fu Wei (Journal of Mountain Science, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Engineered active pure water with reduced hydrogen bonds catalyzes itself in green energy production of oxygen and hydrogen evolution reactions - Shih-Hao Yu; Chun-Chao Chang; Fu-Der Mai; Hui-Yen Tsai; Yu-Chuan Liu (Chemical Engineering Journal, 2023)

A yolk-shell Pd decorated Au@CeO2 with Schottky junction for long-lived charge separation and bandgap optimization to enhance sonodynamic therapy - Weiwei Sheng; Xiunan Wu; Mengying Fu; Cheng Chen; Zetai Bai; Mengyuan Xing; Chun Zhang; Lijuan Chong; Jingjing Li; Fenglei Gao (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Aberrant Histone Modification of TNFAIP3, TLR4, TNIP2, miR-146a, and miR-155 in Major Depressive Disorder - Chu-Chiao Tseng; Shao-Cheng Wang; Yi-Chien Yang; Hung-Chun Fu; Chen-Kai Chou; Hong-Yo Kang; Yi-Yung Hung (Molecular Neurobiology, 2023)

Precursor Development of Sandstone Failure Using IR to Measure the Fractal Characteristics - Hai Sun; Hongyan Zhu; Changyan Shi; Fei Wang; Liqiang Ma; Chun Fu; Pengfei Cui; Yuanyuan Du (Geotechnical and Geological Engineering, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Experimental and numerical study on the ignition delay times of methane/propane mixtures diluted in carbon dioxide - Wenxiang Xia; Chun Zou; Yi Yuan; Rui Fu; Jiacheng Liu; Chao Peng (Fuel, 2023)

Characterization of microbial contamination of retail washed and unwashed shell eggs in Taiwan - Shu-Chen Hsu; Hsiu-Ling Chen; Chin-Fu Chou; Wen-Chun Liu; Chen-Ting Wu (Food Control, 2023)

Fluid hydrodynamics and thermal transports in nanofluids pulsating heat pipes applied for building energy Exploitations: Experimental investigations and full numerical simulations - Wei-Wei Wang; Yong-Juan Song; Chun-Yu Zhang; Hong-Liang Zhang; Yang Cai; Fu-Yun Zhao; Jiang-Hua Guo (Energy and Buildings, 2023)

Ten questions concerning data-driven modelling and forecasting of operational energy demand at building and urban scale - Hussain Kazmi; Chun Fu; Clayton Miller (Building and Environment, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Controlling Dzyaloshinskii-Moriya interaction in a centrosymmetric nonsymmorphic crystal - Zhongyi Zhang; Shengshan Qin; Jiadong Zang; Chen Fang; Jiangping Hu; Fu-Chun Zhang (Science Bulletin, 2023)

Magmatism and thermal effect of the Late Paleoproterozoic layered complex in the Jining terrane, North China Craton: Evidence from magmatic cooling duration and crust-mantle interaction - Wei-Peng Zhu; Wei Tian; Bin Wang; Ming-Yue Gong; Bin Fu; Zi-Long Wang; Chun-Jing Wei (Precambrian Research, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Complete genome sequence of Bacillus cereus 2-6A, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Pacific Ocean - Xuan Zou; Chuan-Lei Suo; Xiao-Mei Geng; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Peng Wang; Mei-Ling Sun (Marine Genomics, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Effects of intra-year precipitation variability on shrub community productivity depend on the annual total rainfall - Ming-Han Yu; Ying-Ying He; Fu-Chong Zhang; Guo-dong Ding; Chun-Yuan Wang (Plant and Soil, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

In Silico Genome-Wide Mining and Analysis of Terpene Synthase Gene Family in Hevea Brasiliensis - Jiahao Liang; De Wang; Xin Li; Weiwen Huang; Chun Xie; Minghui Fu; Hongmei Zhang; Qiong Meng (Biochemical Genetics, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

The Na+/H+ antiporter GbSOS1 interacts with SIP5 and regulates salt tolerance in Gossypium barbadense - Fu-Chun Xu; Mei-Juan Wang; Ya-Wei Guo; Jie Song; Wei Gao; Lu Long (Plant Science, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

Environmental performance of integrated solar flow battery systems - Gonzalo Rodriguez-Garcia; Hui-Chun Fu; Patrick Sullivan; Chih-Jung Chen; Zhaoning Song; Jiquan Chen; Yanfa Yan; Dawei Feng; Song Jin; Ilke Celik (Journal of Cleaner Production, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Tailoring the whole-cell sensing spectrum with cyborgian redox machinery - Kai Yang; Zi-Jie Lu; Tian-Yu Zhu; Jing-Xian Wang; Fu-Qiao Yang; Syed Zaghum Abbas; Jun Zhou; Zhugen Yang; Jian-Li Mi; Sai Kishore Ravi; Yang-Chun Yong (Analytica Chimica Acta, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Towards effective wildlife protection law for marine species in China: A stakeholders’ perspective - Kit Yue Kwan; Ruifang Chen; Chun-Chieh Wang; Shuhao Lin; Lv Wu; Xiaoyong Xie; Zhaohong Weng; Menghong Hu; Haichao Zhou; Zhou Wu; Yijian Fu; Wenquan Zhen; et al. (Frontiers in Marine Science, 2023)
Introduction As one of the megadiverse countries, the effectiveness of wildlife protection in China is of great significance to global biodiversity conservation. With continued evolution and revisions, China’s Wildlife Protection Law has listed over 140 marine species; however, it is still inclined toward terrestrial animals. Methods To narrow the gap between compliance and enforcement, we collected 1,309 effective responses from various coastal cities of China through an anonymous online questionnaire survey, to investigate their exposure, understanding and attitudes toward Wildlife Protection Law for marine species (mWPL). Results Most respondents demonstrated an overall good understanding about the context, necessity and effectiveness of mWPL. The fisher communities were found to be more aware of the dissemination and implementation of mWPL. However, they understood less of the penal system, and exhibited negative attitudes toward the necessity and punishment of the legislation, probably due to the conflicts between resource utilizations and legislative interventions. The participants also indicated that seahorses, horseshoe crabs and corals were commonly subjected to illegal exploitations. Discussion While most respondents suggested greater fines, tighter laws and better public enforcement, we advocate the exploration of bottom-up options such as community engagement and environmental education to improve compliance and implementation of mWPL for the benefit of marine wildlife conservation in China.

Development of species-specific PCR detection for three Mycogone species causing wet bubble disease in white button mushroom - Niu-Niu Shi; Hong-Chun Ruan; Wen-Le Chen; Qiao-Hong Chen; Fu-Ru Chen; Yi-Xin Du (Crop Protection, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Roadside NO2/NOx and primary NO2 from individual vehicles - Peter Brimblecombe; Mengyuan Chu; Chun-Ho Liu; Yunfei Fu; Peng Wei; Zhi Ning (Atmospheric Environment, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

The determining factors of sediment nutrient content and stoichiometry along profile depth in seasonal water - Ruichang Shen; Xingyun Huang; Xiuting Wen; Jie Liu; Hocheol Song; Christoph Weihrauch; Jörg Rinklebe; Hong Yang; Zhifen Yuan; Bofu Zheng; Chun Fu (Science of The Total Environment, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Nonclimacteric ripening characteristics of ‘Jen-Ju Bar’ guava conferred by a defect in the expression of the system-2 ACC synthase gene PgACS1 - Kuo-En Chen; You-Fu Liu; Yu-Chang Liu; Margo Sulistio; Chyi-Chuann Chen; Chun-Ta Wu (Postharvest Biology and Technology, 2023)

Numerical Simulation of a Flat-Sheet Membrane-based Dehumidifier with Various Serpentine Flow Channels - Chun-Han Li; Hsuan-Yu Ho; Tien-Fu Yang; Mohammad Amani; Wei-Mon Yan (International Journal of Refrigeration, 2023)

A new multi-identification system based on a poly(l-cysteine) sensor for simultaneous detection of multiple steroid hormones in serum - Xia Cui; Zhimin Luo; Miao Guo; Jiameng Xu; Lu Wang; Guoning Chen; Gege Wang; Chun Chang; Aiguo Zeng; Jia Zhang; Qiang Fu (Chemical Engineering Journal, 2023)

Construction of strongly coupled few-layer FePSe3-CNT hybrids for high performance potassium-ion storage devices - Yan-Fu Huang; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Lysobacter lactosilyticus sp. nov., a Novel β-Galactosidase Producing Bacterial Strain Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Yu-Huan Wang; Hong-Xing Yang; Shao-Chuang Chuang; Chun-Fu Zhou; Xing Yu; Hao Zhang (Current Microbiology, 2023)

Social isolation does not alter the relationship between flexibility in metabolic rate and growth in grass carp (Ctenopharyngodon idella) under changing food availability - Chun-Yan Sun; Shi-Jian Fu; Ling-Qing Zeng (Journal of Comparative Physiology B, 2023)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

Assessing the impact of rockfall on the retaining structures of a mountain road: a case study in Taiwan - Che-Ming Yang; Chung-Hsun Lee; Chun-Yuan Liu; Wei-Kai Huang; Meng-Chia Weng; Yu-Yao Fu (Landslides, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Characteristics of summer cloud precipitation along latitude 30°N in East Asia derived from Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner measurements - Mengxiao Wang; Yunfei Fu; Chun Zhao; Lei Zhong; Rui Li; Dongyong Wang; Xuexing Qiu; Shengnan Zhou (International Journal of Climatology, 2022)
There has been little systematic analysis of the influence of the three‐step staircase topography on the characteristics of precipitation along latitude 30°N in East Asia. After the distribution of atmospheric climate states over East Asia was analysed, in this study, the climatological characteristics of summer convective and stratiform precipitation on horizontal distribution, vertical structure, and diurnal variation in East Asia were investigated by using a merged dataset derived from the measurements of the Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner from 1998 to 2012 reanalysis datasets. Results indicate that the rain frequency, the mean rain rate, and the maximum echo reflectivity factor show clear differences among the three‐step staircase topography, especially between the first staircase and its eastern region. There are small changes in the echo‐top height, the cloud‐top height, the maximum echo reflectivity factor and its corresponding height from the East China Sea westwards to the eastern part of the first staircase, passing the third staircase and the second staircase along 30°N. However, the rain rate decreased obviously twice westwards along this latitude, which responds to aerosol indirect effect and humidity effect, respectively. The diurnal variation of the convective precipitation reflectivity factor indicated that the development of convection in the eastern part of the first staircase gets at the maximum from the early afternoon to sunset, whereas the strongest echo reflectivity factor of precipitation in the second and third staircases including the East China Sea appears in the early morning, which is consistent with the diurnal variations of the atmospheric circulation.

Lipofundin mediates major inhibition of intravenous propofol on phorbol myristate acetate and Escherichia coli-induced neutrophil extracellular traps - Ming-Shan Chen; Kung-Ssu Yang; Wen-Chun Lin; Chien-Liang Fang; Hsin-Fu Chen; Shew-Meei Sheu (Molecular Biology Reports, 2022)

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer - Gudongze Li; Haoming Chen; Mingyue Xu; Chun Zhao; Lei Zhong; Rui Li; Yunfei Fu; Yanhong Gao (Advances in Atmospheric Sciences, 2022)
The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations and reanalysis data, the simulation can successfully capture the general features of key meteorological fields over the TP despite slightly underestimating the inflow through the southern TP. The results indicate that the complex topography can decrease the inward and outward moisture transport, ultimately increasing the total net moisture transport into the TP by ∼11%. The impacts of complex topography on precipitation are negligible over the TP, but the spatial distributions of precipitation over the Himalayas are significantly modulated. With the inclusion of complex topography, the sharper southern slopes of the Himalayas shift the lifted airflow and hence precipitation northward compared to the smooth topography. In addition, more small-scale valleys are resolved by the inclusion of complex topography, which serve as channels for moisture transport across the Himalayas, further favoring a northward shift of precipitation. Overall, the difference between the two experiments with different topography datasets is mainly attributed to their differing representation of the degree of the southern slopes of the Himalayas and the extent to which the valleys are resolved.

Optimizing Hard Clam Production in Taiwan by Accounting for Nonlinear Effects of Stocking Density and Feed Costs on Farm Output of Clams - Jie-Min Lee; Sheng-Hung Chen; Yi-Chung Lee; Jung-Fu Huang; Christian Schafferer; Chun-Yuan Yeh; Ti-Wan Kung (Fishes, 2022)
Despite mass mortality, hard clams remain among the main cultured shellfish in Taiwan. Using cross-sectional data, this study applies threshold regression modeling with stocking density and feed costs as the threshold variables to explore the nonlinear relationship between input and output factors. The findings show that the production output levels may be increased by different combinations of factor inputs and variations in input factors. More specifically, the higher output levels may be achieved by increasing labor input while reducing capital input factors in farming households with a higher stocking density (HSD > 1,087,870 inds/ha) or higher feed cost (HFC > 13,889 NTD/ha). Farming households with a lower stocking density (LSD ≤ 1,087,870 inds/ha) may enhance production output levels by increasing feed input while reducing capital inputs. Moreover, the maximum output level of HSD and HFC farming households was estimated to reach 9255 kg/ha and 9807 kg/ha, respectively. Results of the production output simulation suggest that the feeding cost per hectare in LSD households should not exceed 25,119 NTD to avoid overfeeding, which may cause culture deterioration and lower survival rates. As such, farmers are advised to adjust their feed costs according to the stocking density to maximize production output.

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Influence of Tidal Cycles on Embryonic Rotation, Hatching and Emergence of Mangrove Horseshoe Crab, Carcinoscorpius rotundicauda - Yang Kuang; Kian Ann Tan; Yijian Fu; Xin Yang; Peng Xu; Wenquan Zhen; Xueping Wang; Xing Huang; Junhua Zhu; Chun-Chieh Wang; Kit Yue Kwan (Journal of Ocean University of China, 2022)

Spatiotemporal Distribution of Asian Horseshoe Crab Eggs Are Highly Intermingled with Anthropogenic Structures in Northern Beibu Gulf, China - Kit Yue Kwan; Yijian Fu; Mufeng Zhong; Yang Kuang; Haiwei Bai; Ce Zhang; Wenquan Zhen; Peng Xu; Chun-Chieh Wang; Junhua Zhu (Journal of Ocean University of China, 2022)

Associations of air pollutants with pneumonia hospital admissions in Qingdao, China: a prospective cohort study - Hai-Tao Wang; Hong Zhang; Fu-Zhong Xue; Lin Zhao; Wu-Chun Cao (Environmental Science and Pollution Research, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

FKgrain: A topography-based software tool for grain segmentation and sizing using factorial kriging - Fu-Chun Wu; Chi-Kuei Wang; Hong Ping Lo (Earth Science Informatics, 2021)

WRF/UCM simulations of the impacts of urban expansion and future climate change on atmospheric thermal environment in a Chinese megacity - Yang Zhao; Lei Zhong; Yaoming Ma; Yunfei Fu; Mingxing Chen; Weiqiang Ma; Chun Zhao; Ziyu Huang; Keqi Zhou (Climatic Change, 2021)

Label-Free Quantitative Proteomic Analysis of Three Strains of Viscerotropic Leishmania Isolated from Patients with Different Epidemiological Types of Visceral Leishmaniasis in China - Fu-rong Wei; Chun-hua Gao; Jun-yun Wang; Yue-tao Yang; Feng Shi; Bin Zheng (Acta Parasitologica, 2021)

Methacrylic functionalized hybrid carbon nanomaterial for the selective adsorption and detection of progesterone in wastewater - Xia Cui; Hua Shu; Lu Wang; Guoning Chen; Jili Han; Qianqian Hu; Kamran Bashir; Zhimin Luo; Chun Chang; Jia Zhang; Qiang Fu (Environmental Science and Pollution Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

Qingbo, a common cyprinid fish, responds diversely in behavior and locomotion to predators with different hunting modes - Cheng Fu; Lian-Chun Yi; Wen-Pei Wu; Chun-Xiao Sun; Rui-Na Liu; Shi-Jian Fu (Fish Physiology and Biochemistry, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Neuronal Exosomes Secreted under Oxygen–Glucose Deprivation/Reperfusion Presenting Differentially Expressed miRNAs and Affecting Neuronal Survival and Neurite Outgrowth - Chien-Sung Chiang; Ssu-Ju Fu; Chia-Lang Hsu; Chung-Jiuan Jeng; Chih-Yung Tang; Yi-Shuian Huang; Sung-Chun Tang (NeuroMolecular Medicine, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

The Integration of Carbon Price Between European and Chinese Markets: What are the Implications? - Yunpeng Wang; Qiang Fu; Chun-Ping Chang (International Journal of Environmental Research, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Effect of chemical additives on the consolidation behavior of slurries - Jin-chun Chai; Hong-tao Fu (Marine Georesources & Geotechnology, 2021)

Kynurenine pathway as alternative biosynthetic pathway for fusaric acid in Fusarium oxysporum f.sp. cubense - Tao Zeng; Hui-Cai Zeng; Mei-Ying Fu; Kai-Kun Huang; Jian-Chun Guo; Xin-Wen Hu (Australasian Plant Pathology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

The ankyrin repeat-containing protein MdANK2B regulates salt tolerance and ABA sensitivity in Malus domestica - Fu-jun Zhang; Yin-huan Xie; Han Jiang; Xun Wang; Yu-Jin Hao; Zhenlu Zhang; Chun-Xiang You (Plant Cell Reports, 2021)

Engrafted primary type-2 astrocytes improve the recovery of the nigrostriatal pathway in a rat model of Parkinson's disease - Yanyun Sun; Xiao-jun Lu; Xinghui Fu; Ye Zhang; Yan Zhan; Jiabing Liu; Lingxia Zhao; Chun-lin Xia (Molecular and Cellular Biochemistry, 2021)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Effects of climate variability and land use/land cover change on the Daihai wetland of central Inner Mongolia over the past decades - Xi Chun; Fu-ying Qin; Hai-jun Zhou; Dan Dan; Ying-ying Xia; Khukhuudei Ulambadrakh (Journal of Mountain Science, 2020)

Petrogenesis of post-collisional magmatism at the Carboniferous–Permian boundary in central Inner Mongolia, NE China: insights into when the Hegenshan Ocean closed? - Lu Lu; Yong Qin; Kai-Jun Zhang; Chun-Yuan Han; Zhuang-Fu Li; Tao Wei; Zheng-Hui Qu; Yong-Zhong Xu (International Geology Review, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Model tests on performance of offshore wind turbine with suction caisson foundation in sand - Hai-lei Kou; Dan-liang Yang; Wang-chun Zhang; Yi-fan Wu; Qiang Fu (Marine Georesources & Geotechnology, 2020)

Further evidence for paternal DNA transmission in gynogenetic grass carp - Zhuangwen Mao; Yeqing Fu; Shi Wang; Yude Wang; Kaikun Luo; Chun Zhang; Min Tao; Shaojun Liu (Science China Life Sciences, 2020)

Silencing of long non-coding RNA CRNDE promotes autophagy and alleviates neonatal hypoxic-ischemic brain damage in rats - Chun-Hua Fu; Fang-Fang Lai; Sai Chen; Cai-Xia Yan; Bing-Hong Zhang; Cheng-Zhi Fang; Gao-Hua Wang (Molecular and Cellular Biochemistry, 2020)

The effect of baicalin on microRNA expression profiles in porcine aortic vascular endothelial cells infected by Haemophilus parasuis - Shulin Fu; Jun Liu; Jianfeng Xu; Sanling Zuo; Yunfei Zhang; Ling Guo; Yinsheng Qiu; Chun Ye; Yu Liu; Zhongyuan Wu; Yongqing Hou; Chien-An Andy Hu (Molecular and Cellular Biochemistry, 2020)

Efficient removal of antibiotic oxytetracycline from water using optimized montmorillonite-supported zero-valent iron nanocomposites - Mai Lien Tran; Si-Wei Deng; Chun-Chieh Fu; Ruey-Shin Juang (Environmental Science and Pollution Research, 2020)

Spatio-temporal variations of vegetation carbon use efficiency and potential driving meteorological factors in the Yangtze River Basin - Xu-chun Ye; Fu-hong Liu; Zeng-xin Zhang; Chong-yu Xu; Jia Liu (Journal of Mountain Science, 2020)

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis - Li Shang; Liren Yang; Wenfang Yang; Liyan Huang; Cuifang Qi; Zixuan Yang; Zhuxuan Fu; Mei Chun Chung (Environmental Science and Pollution Research, 2020)
The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children’s cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient was extracted, conversed, and synthesized by random effects meta-analysis. Meanwhile, qualitatively describe would be used for some studies which cannot be synthesized quantitatively for lack of quantity or methods inconsistency. Finally, a total of 3848 citations were searched, and only 10 studies were included. We estimated that per 10 μg/m 3 increase of NO 2 during pregnancy was associated with a − 0.76 point decrease in global psychomotor (95% CI, − 1.34, − 0.18) and a − 0.62 point decrease in fine psychomotor for children (95% CI, − 1.09, − 0.16). But no significant association found in general cognitive and language. In addition, through the literature review, it seemed that prenatal exposure to NO 2 might cause adverse impacts on children’s attention, IQ, and different behaviors, but this requires confirmation from further researches. Our study indicated that prenatal exposure to NO 2 seems to be associated with impaired neural development for children, especially for fine psychomotor. However, further studies are needed for determining the effects of prenatal air pollution exposure on attention, IQ, and behavior.

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

Transcriptome-wide identification, classification, and characterization of NAC family genes in Bamboo Bambusa emeiensis - Yuanqiu Li; Chaobing Luo; Ying Chen; Chun Fu; Yaojun Yang (Acta Physiologiae Plantarum, 2020)

Disseminated cutaneous herpes zoster and multiple cerebral infarcts in an adult with diabetes mellitus - Chun-Fu Lin; Chien-Tai Hong; Wei-Hwa Lee; Dean Wu; Chaur-Jong Hu; Chen-Chih Chung (Journal of NeuroVirology, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Panax notoginsenoside Rb1 Restores the Neurotrophic Imbalance Following Photothrombotic Stroke in Rats - Chun-Yan Yang; Jian-Yu Yang; Yun-Xia Xiong; Xue-Feng Zhuang; Hui Su; Sheng Hu; Jia-Qing Ma; Xin-Fu Zhou; Hai-Yun Luo; Jun Sun (Neurotoxicity Research, 2019)

Relationship between Extreme Precipitation and Temperature in Two Different Regions: The Tibetan Plateau and Middle-East China - Rui Wang; Tao Xian; Mengxiao Wang; Fengjiao Chen; Yuanjian Yang; Xiangdong Zhang; Rui Li; Lei Zhong; Chun Zhao; Yunfei Fu (Journal of Meteorological Research, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Exponential rolling circle amplification coupled with lateral flow dipstick strips as a rapid and sensitive method for the field detection of Karlodinium veneficum - Fu Guo Liu; Guo Fu Chen; Chun Yun Zhang; Yuan Yuan Wang; Jin Zhou (Journal of Applied Phycology, 2019)

Survey of lead concentration in tap water on a university campus - Fu-Chun Chang; Yi-Pin Lin (Environmental Science and Pollution Research, 2019)

Transcriptome-based Discovery of AP2/ERF tRanscription Factors and Expression Profiles Under Herbivore Stress Conditions in Bamboo (Bambusa emeiensis) - Yuanqiu Li; Chaobing Luo; Ying Chen; Ximeng Xiao; Chun Fu; Yaojun Yang (Journal of Plant Biology, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Cold-inducible MaC2H2s are associated with cold stress response of banana fruit via regulating MaICE1 - Yan-Chao Han; Chang-Chun Fu (Plant Cell Reports, 2019)

Skinfold thickness for rivastigmine patch application in Alzheimer’s disease - Ping-Song Chou; Kai-Ming Jhang; Ling-Chun Huang; Wen-Fu Wang; Yuan-Han Yang (Psychopharmacology, 2019)

Timing and genesis of Cu–(Au) mineralization in the Khetri Copper Belt, northwestern India: constraints from in situ U–Pb ages and Sm–Nd isotopes of monazite-(Ce) - Xiao-Chun Li; Mei-Fu Zhou; A. E. Williams-Jones; Yue-Heng Yang; Jian-Feng Gao (Mineralium Deposita, 2019)

Removal of metronidazole and amoxicillin mixtures by UV/TiO2 photocatalysis: an insight into degradation pathways and performance improvement - Mai Lien Tran; Chun-Chieh Fu; Ruey-Shin Juang (Environmental Science and Pollution Research, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Impacts of Climate Change and Varietal Replacement on Winter Wheat Phenology in the North China Plain - Zhan-biao Wang; Jing Chen; Wen-jie Tong; Chang-chun Xu; Fu Chen (International Journal of Plant Production, 2018)

Silencing of GbANS reduces cotton resistance to Verticillium dahliae through decreased ROS scavenging during the pathogen invasion process - Lu Long; Jing-Ruo Zhao; Fu-Chun Xu; Wen-Wen Yang; Peng Liao; Ya Gao; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Removal of metronidazole by TiO2 and ZnO photocatalysis: a comprehensive comparison of process optimization and transformation products - Mai Lien Tran; Chun-Chieh Fu; Ruey-Shin Juang (Environmental Science and Pollution Research, 2018)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

The impacts of environmental governance on political turnover of municipal party secretary in China - Gen-Fu Feng; Minyi Dong; Jun Wen; Chun-Ping Chang (Environmental Science and Pollution Research, 2018)

Transcranial Ultrasound Stimulation Improves Long-Term Functional Outcomes and Protects Against Brain Damage in Traumatic Brain Injury - Szu-Fu Chen; Wei-Shen Su; Chun-Hu Wu; Tsuo-Hung Lan; Feng-Yi Yang (Molecular Neurobiology, 2018)

Identification of Fusarium species associated with soybean root rot in Sichuan Province, China - Xiaoli Chang; Hao Dai; Duiping Wang; Huanhuan Zhou; Wanqin He; Yao Fu; Faisal Ibrahim; You Zhou; Guoshu Gong; Jing Shang; Jizhi Yang; Xiaoling Wu; et al. (European Journal of Plant Pathology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

A heuristic probabilistic approach to estimating size-dependent mobility of nonuniform sediment - Befekadu Taddesse Woldegiorgis; Fu-Chun Wu; Ann Van Griensven; Willy Bauwens (Stochastic Environmental Research and Risk Assessment, 2018)

Transdimensional Bayesian inversion of time-domain airborne EM data - Zong-Hui Gao; Chang-Chun Yin; Yan-Fu Qi; Bo Zhang; Xiu-Yan Ren; Yong-Chao Lu (Applied Geophysics, 2018)

Prodigiosin stimulates endoplasmic reticulum stress and induces autophagic cell death in glioblastoma cells - Shu-Yu Cheng; Nan-Fu Chen; Hsiao-Mei Kuo; San-Nan Yang; Chun-Sung Sung; Ping-Jyun Sung; Zhi-Hong Wen; Wu-Fu Chen (Apoptosis, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

Novel method for iron recovery from hazardous iron ore tailing with induced carbothermic reduction-magnetic flocculation separation - Shao-Jun Bai; Chun-Long Li; Xiang-Yu Fu; Chao Lv; Shu-Ming Wen (Clean Technologies and Environmental Policy, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Uranium-lead dating of hydrothermal zircon and monazite from the Sin Quyen Fe-Cu-REE-Au-(U) deposit, northwestern Vietnam - Xiao-Chun Li; Mei-Fu Zhou; Wei Terry Chen; Xin-Fu Zhao; MyDung Tran (Mineralium Deposita, 2018)

3D forward modeling and response analysis for marine CSEMs towed by two ships - Bo Zhang; Chang-Chun Yin; Yun-He Liu; Xiu-Yan Ren; Yan-Fu Qi; Jing Cai (Applied Geophysics, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

Coamorphous Loratadine-Citric Acid System with Enhanced Physical Stability and Bioavailability - Jin Wang; Ruimiao Chang; Yanan Zhao; Jiye Zhang; Ting Zhang; Qiang Fu; Chun Chang; Aiguo Zeng (AAPS PharmSciTech, 2017)

Detection of exercise periodic breathing using thermal flowmeter in patients with heart failure - Tieh-Cheng Fu; Wen-Chen Lin; Jong-Shyan Wang; Chao-Hung Wang; Chun-Tien Chang; Cheng-Lun Tsai; Yun-Shien Lee; Kang-Ping Lin (Medical & Biological Engineering & Computing, 2017)

The role of solubility on the rejection of trace organics by nanofiltration membrane: exemplified with disinfection by-products - Fan-xin Kong; Xiao-mao Wang; Hong-wei Yang; Jin-fu Chen; Chun-mei Guo; Tong Zhang; Yuefeng F. Xie (Environmental Science and Pollution Research, 2017)

Long-Term Generation Scheduling of Hydropower System Using Multi-Core Parallelization of Particle Swarm Optimization - Sheng-li Liao; Ben-xi Liu; Chun-tian Cheng; Zhi-fu Li; Xin-yu Wu (Water Resources Management, 2017)

Resveratrol protects the loss of connexin 43 induced by ethanol exposure in neonatal mouse cardiomyocytes - Su Tu; Fu-tao Cao; Xiao-chun Fan; Cheng-jian Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

An economic analysis of hard clam (Meretrix meretrix) farmer polyculture with milkfish (Chanos chanos), silver sea bream (Rhabdosargus sarba), and shrimps at different hard clam stocking densities: a case study of Yunlin County, Taiwan - Chun-Yuan Yeh; Jung-Fu Huang; Jie-Min Lee; Christian Schafferer (Aquaculture International, 2017)

Full-scale field load testing of long drilled shafts with enlarged base constructed in marine sediment - Kai-Fu Liu; Xin-Yu Xie; Zhe Luo; Qing-Hong Hu; Chun-Xia Huang (Marine Georesources & Geotechnology, 2017)

Platelet receptor Gene (P2Y12, P2Y1) and platelet glycoprotein Gene (GPIIIa) polymorphisms are associated with antiplatelet drug responsiveness and clinical outcomes after acute minor ischemic stroke - Xingyang Yi; Qiang Zhou; Chun Wang; Jing Lin; Ping Liu; Cheng Fu (European Journal of Clinical Pharmacology, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Soil application of zinc fertilizer could achieve high yield and high grain zinc concentration in maize - Dun-Yi Liu; Wei Zhang; Peng Yan; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Mycorrhizal colonization status of lowland rice (Oryza sativa L.) in the southeastern region of China - Xun-Wen Chen; Fu-Yong Wu; Hui Li; Wai-Fung Chan; Sheng-Chun Wu; Ming-Hung Wong (Environmental Science and Pollution Research, 2017)

Papaya CpERF9 acts as a transcriptional repressor of cell-wall-modifying genes CpPME1/2 and CpPG5 involved in fruit ripening - Chang-Chun Fu; Yan-Chao Han; Xiu-Ye Qi; Wei Shan; Jian-Ye Chen; Wang-Jin Lu; Jian-Fei Kuang (Plant Cell Reports, 2016)

Double-stranded-RNA-specific adenosine deaminase 1 (ADAR1) is proposed to contribute to the adaptation of equine infectious anemia virus from horses to donkeys - Yan-Dong Tang; Xiang Zhang; Lei Na; Xue-feng Wang; Li-Hua Fu; Chun-Hui Zhu; Xiaojun Wang; Jian-Hua Zhou (Archives of Virology, 2016)

A sensitive immunochromatographic assay using colloidal gold–antibody probe for rapid detection of fumonisin B 1 in corn - Xi-Chun Wang; Hai-Xin Fan; Meng-Xue Fan; Fu-Hui Li; Shi-Bin Feng; Jin-Chun Li; Jin-Jie Wu; Yu Li; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Public health implications of social media use during natural disasters, environmental disasters, and other environmental concerns - Kathryn C. Finch; Kassandra R. Snook; Carmen H. Duke; King-Wa Fu; Zion Tsz Ho Tse; Atin Adhikari; Isaac Chun-Hai Fung (Natural Hazards, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

Effects of Dietary Selenium Against Lead Toxicity Are Related to the Ion Profile in Chicken Muscle - Xi Jin; Chun Peng Liu; Xiao Hua Teng; Jing Fu (Biological Trace Element Research, 2016)

The disintegrin, trimucrin, suppresses LPS-induced activation of phagocytes primarily through blockade of NF-κB and MAPK activation - Yu-Chun Hung; Chun-Chieh Hsu; Ching-Hu Chung; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Development of a quantitative PCR for detection and quantification of Prorocentrum donghaiense - Chun Yun Zhang; Guo Fu Chen; Jin Zhou; Yuan Yuan Wang; Dou Ding Lu (Journal of Applied Phycology, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Construction and pilot screening of a signature-tagged mutant library of Sinorhizobium fredii - Dan Wang; Yuan Chun Wang; Li Juan Wu; Jian Xin Liu; Pan Zhang; Jian Jiao; Hui Yan; Tao Liu; Chang Fu Tian; Wen Xin Chen (Archives of Microbiology, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

In situ Sr isotope analysis of apatite by LA-MC-ICPMS: constraints on the evolution of ore fluids of the Yinachang Fe-Cu-REE deposit, Southwest China - Xin-Fu Zhao; Mei-Fu Zhou; Jian-Feng Gao; Xiao-Chun Li; Jian-Wei Li (Mineralium Deposita, 2015)

Reflux characteristics of 113 GERD patients with abnormal 24-h multichannel intraluminal impedance-pH tests - Yuan-yuan Nian; Cheng Feng; Fu-chun Jing; Xue-qin Wang; Jun Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

Application of reverse dot blot hybridization to simultaneous detection and identification of harmful algae - Guo Fu Chen; Chun Yun Zhang; Yuan Yuan Wang; Wen Chen (Environmental Science and Pollution Research, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Experimental Study of the Effect on Bone Metabolism and Bone Histomorphometry of Osteoporosis Rats with Birdpecking and Revolving Moxibustion on Twelve Back-Shu Points - Hong-Shi Zhang; Tie Li; Xing-Shan Liu; Fu-Chun Wang; Xin Yao; Li Yan; Wu-Jin Liang (Cell Biochemistry and Biophysics, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Dating thin zircon rims by NanoSIMS: the Fengtien nephrite (Taiwan) is the youngest jade on Earth - Tzen-Fu Yui; Tadashi Usuki; Chun-Yen Chen; Akizumi Ishida; Yuji Sano; Kenshi Suga; Yoshiyuki Iizuka; Chih-Tung Chen (International Geology Review, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

Sodium fluoride induces apoptosis in the kidney of rats through caspase-mediated pathways and DNA damage - Guo Hua Song; Ji Ping Gao; Chun Fang Wang; Chao Yang Chen; Xiao Yan Yan; Min Guo; Yu Wang; Fu Bing Huang (Journal of Physiology and Biochemistry, 2014)

The cellular community in the intestine of the shrimp Penaeus penicillatus and its culture environments - Chun-zhong Wang; Guo-rong Lin; Tao Yan; Zhi-peng Zheng; Bin Chen; Fu-lin Sun (Fisheries Science, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Two new eunicellin-based diterpenoids from the South China Sea gorgonian Muricella sibogae Nutting - Yuan-Ming Zhou; Min Chen; Xiu-Mei Fu; Yu-Chun Fang; Chang-Yun Wang (Natural Product Research, 2014)

Interaction network analysis revealed biomarkers in myocardial infarction - Tong Zhang; Li-Li Zhao; Zhuo-Ran Zhang; Pei-De Fu; Zhen-Dong Su; Li-Chun Qi; Xue-Qi Li; Yu-Mei Dong (Molecular Biology Reports, 2014)

Factors determining species displacement of related predatory mite species (Acari: Phytoseiidae) - Tetsuo Gotoh; Masumi Hanawa; Sayaka Shimazaki; Natsuki Yokoyama; Chun-Qing Fu; Reo Sugawara; Shuichi Yano (Experimental and Applied Acarology, 2014)

Distribution of Polychlorinated Biphenyls in Soil Around Three Typical Industrial Sites in Beijing, China - Yong-Fei Zhang; Shan Fu; Yuan Dong; Hai-Feng Nie; Zheng Li; Xin-Chun Liu (Bulletin of Environmental Contamination and Toxicology, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Zinc fertilizer placement affects zinc content in maize plant - Yue-Qiang Zhang; Li-Li Pang; Peng Yan; Dun-Yi Liu; Wei Zhang; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Evaluation of Locations for Small Wind Turbines in Costal Urban Areas Based on a Wind Energy Potential Map - Chun-Ming Hsieh; Chuan-Kang Fu (Environmental Modeling & Assessment, 2013)

A new triterpene saponin from the roots of Ilex pubescens - Zhong-Liu Zhou; Zong-Cai Feng; Chun-Yan Fu; Li Zeng (Natural Product Research, 2013)

Development of rRNA-targeted probes for detection of Prorocentrum micans (Dinophyceae) using whole cell in situ hybridization - Guo Fu Chen; Yang Liu; Chun Yun Zhang; Chao Shuai Ma; Bao Yu Zhang; Guang Ce Wang; Zhong Xu; Dou Ding Lu (Journal of Applied Phycology, 2013)

Tai Chi practitioners have better postural control and selective attention in stepping down with and without a concurrent auditory response task - Xi Lu; Ka-Chun Siu; Siu N. Fu; Christina W. Y. Hui-Chan; William W. N. Tsang (European Journal of Applied Physiology, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

The reduction in zinc concentration of wheat grain upon increased phosphorus-fertilization and its mitigation by foliar zinc application - Yue-Qiang Zhang; Yan Deng; Ri-Yuan Chen; Zhen-Ling Cui; Xin-Ping Chen; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

A comparison of the ultrastructure and composition of fruits’ cuticular wax from the wild-type ‘Newhall’ navel orange (Citrus sinensis [L.] Osbeck cv. Newhall) and its glossy mutant - De-Chun Liu; Qiong Zeng; Qing-Xun Ji; Chuan-Fu Liu; Shan-Bei Liu; Yong Liu (Plant Cell Reports, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

A novel lignan glycoside with antioxidant activity from Tinospora sagittata var. yunnanensis - Xiang-Zhong Huang; Chun-Mei Cheng; Yun Dai; Guang-Miao Fu; Jun-Ming Guo; Hui Liang; Chao Wang (Natural Product Research, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Low BDNF is associated with cognitive impairment in chronic patients with schizophrenia - Xiang Yang Zhang; Jun Liang; Da Chun Chen; Mei Hong Xiu; Fu De Yang; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

A spatial aggregation index for effective fallow decision in paddy irrigation demand planning - Ming-Daw Su; Mei-Chun Lin; Chun-Hung Lin; Shih-Fu Wang; Tzai-Hung Wen; Hsin-I Hsieh (Paddy and Water Environment, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Overexpression of a vacuolar H+-pyrophosphatase and a B subunit of H+-ATPase cloned from the halophyte Halostachys caspica improves salt tolerance in Arabidopsis thaliana - You-zhen Hu; You-ling Zeng; Bo Guan; Fu-chun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A DNA vaccine expressing CFP21 and MPT64 fusion protein enhances BCG-induced protective immunity against Mycobacterium tuberculosis infection in mice - Chun Wang; Zhenhua Chen; Ruiling Fu; Ying Zhang; Lingxia Chen; Li Huang; Jinjin Li; Chunwei Shi; Xionglin Fan (Medical Microbiology and Immunology, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Molecular Identification and Physiological Characterization of a Putative Novel Plasma Membrane Protein from Arabidopsis Involved in Glucose Response - Moon-Soo Chung; Ping Huang; Chan Man Ha; Ji Hyung Jun; Sung-Ju Ahn; Fu-chun Zhang; Hyun-Jong Bae; Baik Ho Cho; Cheol Soo Kim (Journal of Plant Biology, 2011)

Stability Kinetics of Influenza Vaccine Coated onto Microneedles During Drying and Storage - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Cumulate hornblendite enclaves in diorite–porphyrite intrusions from the Shuangyashan, Northeast China, and implications for the transition from lower crust to upper mantle in subduction setting - Lei Zhang; Bao-Fu Han; Chun-Jing Wei; Gui-Ming Shu (International Journal of Earth Sciences, 2011)

Identification of differentially expressed transcripts involved in the salt-stress response of Salsola ferganica by suppression subtractive hybridization - Bo Guan; Gang-qiang Jiang; Ying-xin Wang; Zhi-cai Wang; Yakupjan Haxim; Qian Bao; You-zhen Hu; Fu-chun Zhang; Yan Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Targeted antitumor effect induced by hTERT promoter mediated ODC antisense adenovirus - Wei Wang; Bin Jin; Wei Li; Chun-Xiao Xu; Fu-Ai Cui; Bin Liu; Yun-Fei Yan; Xian-Xi Liu; Xiu-Li Wang (Molecular Biology Reports, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

Formulation of Microneedles Coated with Influenza Virus-like Particle Vaccine - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (AAPS PharmSciTech, 2010)

NP-184[2-(5-methyl-2-furyl) benzimidazole], a novel orally active antithrombotic agent with dual antiplatelet and anticoagulant activities - Heng-Lan Kuo; Jin-Cherng Lien; Ching-Hu Chung; Chien-Hsin Chang; Shyh-Chyi Lo; I-Chun Tsai; Hui-Chin Peng; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Microarray Profile of Brain Aging-Related Genes in the Frontal Cortex of SAMP8 - Shao-Chun Chen; Gang Lu; Chu-Yan Chan; Yangchao Chen; Hua Wang; David Tai-Wai Yew; Zhong-Tang Feng; Hsiang-Fu Kung (Journal of Molecular Neuroscience, 2010)

Isopentenyl transferase gene (ipt) downstream transcriptionally fused with gene expression improves the growth of transgenic plants - Jian-Chun Guo; Rui-Jun Duan; Xin-Wen Hu; Kai-Mian Li; Shao-Ping Fu (Transgenic Research, 2010)

Transgenic RNAi-mediated reduction of LZP3 in Lagurus lagurus oocytes results in decreased fertilization ability in IVF - Shu Zhen Zhuang; Xin Jian Li; Ai Lian Zhang; Ji Ma; Yao Hu Zheng; Fu Chun Zhang (Molecular Biology Reports, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

Rapid screening of tetrodotoxin in urine and plasma of patients with puffer fish poisoning by HPLC with creatinine correction - Chung-Him Yu; Chun-Fai Yu; Sidney Tam; Peter Hoi-Fu Yu (Food Additives & Contaminants: Part A, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Hypoxic training increases metabolic enzyme activity and composition of α-myosin heavy chain isoform in rat ventricular myocardium - Ming-Chun Cai; Qing-Yuan Huang; Wei-Gong Liao; Zhou Wu; Fu-Yu Liu; Yu-Qi Gao (European Journal of Applied Physiology, 2010)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Detrital zircon evidence for the antiquity of Taiwan - Ching-Ying Lan; Tadashi Usuki; Kuo-Lung Wang; Tzen-Fu Yui; Kazuaki Okamoto; Yuan-Hsi Lee; Takafumi Hirata; Yoshitaka Kon; Yuji Orihashi; Juhn G. Liou; Chun-Sun Lee (Geosciences Journal, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Co-localization of hyperphosphorylated tau and caspases in the brainstem of Alzheimer’s disease patients - Maria Sen Mun Wai; Yong Liang; Chun Shi; Eric Y. P. Cho; Hsiang-fu Kung; David T. Yew (Biogerontology, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Studies on the Toxicological Effects of PFOA and PFOS on Rats Using Histological Observation and Chemical Analysis - Lin Cui; Qun-fang Zhou; Chun-yang Liao; Jian-jie Fu; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2009)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Ambient air monitoring of Beijing MSW logistics facilities in 2006 - Chun-Ping Li; Guo-Xue Li; Yi-Ming Luo; Yan-Fu Li (Environmental Monitoring and Assessment, 2008)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

Differentiation of commercial strains of Agaricus species in China with inter-simple sequence repeat marker - Xue-Juan Guan; Lu Xu; Yan-Chun Shao; Zhuo-Ren Wang; Fu-Sheng Chen; Xin-Chang Luo (World Journal of Microbiology and Biotechnology, 2008)

Research on the Components of Dust Fall in Hohhot in Comparison with Surface Soil Components in Different Lands of Inner Mongolia Plateau - Chun-xing Hai; Chun-shin Yuan; Guang-tong Liu; Xiao-jia Li; Fu Zhang; Xiu-jiang Zhang (Water, Air, & Soil Pollution, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Inhibition by oxytocin of methamphetamine-induced hyperactivity related to dopamine turnover in the mesolimbic region in mice - Jia Qi; Jing-Yu Yang; Ming Song; Yan Li; Fang Wang; Chun-Fu Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Protective effects of ginsenoside Rg3 against cyclophosphamide-induced DNA damage and cell apoptosis in mice - Qiu Hua Zhang; Chun Fu Wu; Lian Duan; Jing Yu Yang (Archives of Toxicology, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

A case of chylothorax treated curatively with Sapylin, a streptococcus preparation - Zhi-hao Xu; Chun-fu Wang; Yue-qin Zhang; Hua-hao Shen; Feng Xu (Journal of Zhejiang University-SCIENCE B, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Imbalanced free radicals and antioxidant defense systems in schizophrenia: A comparative study - Hui-chun Li; Qiao-zhen Chen; Ying Ma; Jun-fu Zhou (Journal of Zhejiang University-SCIENCE B, 2006)

Expression of α-dystrobrevin in blood-tissue barriers: sub-cellular localisation and molecular characterisation in normal and dystrophic mice - Chun Fu Lien; Diana Hazai; Davy Yeung; Juraini Tan; Ernst-Martin Füchtbauer; Veronika Jancsik; Dariusz C. Górecki (Cell and Tissue Research, 2006)

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis - Shu-Chun Teng; Kou-Juey Wu; Shun-Fu Tseng; Chui-Wei Wong; Li Kao (Journal of Molecular Histology, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Salicylic Acid Enhances Jaceosidin and Syringin Production in Cell Cultures of Saussurea medusa - Zhen-Zhen Yu; Chun-Xiang Fu; Ying-Shan Han; Yong-Xing Li; De-Xiu Zhao (Biotechnology Letters, 2006)

A Facile Method for Preparation of Polymerizable, Optically Active Ketoprofen Prodrug by Irreversible Lipase-catalysed Resolution - Xiao-Qing Cai; Zhi-Chun Chen; Na Wang; Xian-Fu Lin (World Journal of Microbiology and Biotechnology, 2006)

A comparison between hairy root cultures and wild plants of Saussurea involucrata in phenylpropanoids production - Chun-Xiang Fu; Yan-jun Xu; De-Xiu Zhao; Feng Shan Ma (Plant Cell Reports, 2006)

Cellular aggregate size as the critical factor for flavonoid production by suspension cultures of Saussurea medusa - Chun-xiang Fu; De-xiu Zhao; Yan Huang; Feng-shan Ma (Biotechnology Letters, 2005)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Quantification Analysis for Saccadic Eye Movements - Tainsong Chen; Yung-Fu Chen; Chun-Hsien Lin; Tzu-Tung Tsai (Annals of Biomedical Engineering, 1998)